Justice for Children: Exploring Juvenile Criminal Law in Indonesia - Widowati, Widowati (Westscience Press, 2024)
AJuvenile justice is a significant aspect of any criminal justice system, especially in countries where children's rights are enshrined in law. In Indonesia, the juvenile criminal justice system has evolved considerably, with a focus on rehabilitation and protection of the child’s welfare. This article delves into Indonesia's juvenile criminal laws, specifically Law No. 11 of 2012 on the Juvenile Criminal Justice System, which introduced a more restorative approach to dealing with child offenders. The paper explores how Indonesia balances punishment with rehabilitation, analyzing the effectiveness of this system compared to global standards. By examining case studies, legal frameworks, and rehabilitation programs, the study evaluates how well these laws serve the interests of both society and juvenile offenders. The article also discusses challenges such as inconsistencies in implementation, socio-economic disparities, and public perceptions of juvenile justice. Finally, recommendations are provided to enhance the efficiency and fairness of juvenile criminal law in Indonesia.